MITRAGYNINE PERCENTAGES OF VARIOUS KRATOM VARIANTS SEIZED IN INDONESIA: A QUANTITATIVE ANALYSIS USING LIQUID CHROMATOGRAPHY-PHOTO DIODE ARRAY DETECTOR - TANTI; LALANGI, CHRISTIEN ANDRIYANI; ARFIYANI, ERI; NINGTIAS, WIDIANTI; MAULIDA, ERLANA NINDYA (International Journal of Applied Pharmaceutics, 2021)
Objective: This study details the determination of mitragynine in various kratom samples using the thin-layer chromatography (TLC) technique and validation of analytical methods for quantifying the concentration of mitragynine in various kratom samples using liquid chromatography with photodiode array detector (LC-PDA). Methods: TLC technique using n-hexane: ethyl acetate: ammonia 25% (30: 15: 1 v/v/v) was applied to isolate mitragynine from kratom samples. Several interesting spots obtained were visualized under UV light at 254 nm. Samples were also prepared with organic solvent extraction directly prior to LC analysis (non-isolation method of preparation) to quantify the concentration of mitragynine. Mobile phases used were acetonitrile (MP A) and 0.1% formic acid in water (MP B). Samples and standards were run by gradient elution with a flow rate of 0.3 ml/min, detection using PDA detector at 254 nm. Results: Mitragynine was successfully isolated from kratom samples in Rf 0.50 by TLC system applied. The validation of analytical methods for mitragynine passed the acceptance criteria as described by UNODC Guidance. The concentration of mitragynine in various kratom samples seized in Indonesia ranged from 0.37%-1.70% (%w/w). Conclusion: Both TLC and LC analytical methods could be applied to determine and quantify the concentration of mitragynine in each examined sample, respectively.